The 2021 German Federal Election
XXIII, 444 p. 50 illus., 33 illus. in color.
Keywords: “In democracies, elections are routine, but can be markers of significant change. The 2021 German federal election fits both characteristics, and here top-notch scholars show why. They critically assess issues and challenges current-day Germany faces as it, once again, navigates a new era. Their authoritative analyses on a wide range of topics are a stimulating read.” — Helga Welsh, Wake Forest University, USA “The 2021 German Bundestag election represents a watershed: the end of the Merkel era and the inauguration of the first national traffic-light coalition. This book offers a comprehensive account of the developments leading up to this significant change in German politics. It’s an essential reading for anybody interested in German politics.” —Thomas Poguntke, Heinrich Heine University Düsseldorf, Germany “This excellent essay collection provides a comprehensive account of how German politics changed with the 2021 national elections. Covering the evolution of political parties and key issues in politics, it also includes changes in foreign relations. The book should be the new key reference for all students of contemporary German and European politics and Transatlantic relations.” —Christiane Lemke, Leibniz University Hannover, Germany The German Federal Election of 2021 was one of the most open and competitive in the post-war era. This book provides a systematic analysis of its domestic and international context, the shifting balance of the political parties, the election strategies and campaign themes, along with the challenges of government formation. An international array of scholars from Europe and North America have contributed specially commissioned chapters on their principal areas of research. The discussion of individual topics is combined with sufficient background information so as to be accessible to readers who may not have detailed knowledge of German politics. The bookalso includes images of popular campaign posters, making it an indispensable reference tool. Ross Campbell is Senior Lecturer in Political Science at the University of the West of Scotland, UK. Louise K. Davidson-Schmich is Professor of Political Science at the University of Miami in Coral Gables, Florida, USA.